Growth Performance of Sand Lobster (Panulirus homarus) with Different Calcium Carbonate Additions - Dzaky, Muhammad; Lesmana, Dudi; Mulyana, Mulyana (JURNAL MINA SAINS, 2024)
Spiny lobster (Panulirus homarus) is an invertebrate with a hard outer shell and is classified as part of the Arthropoda phylum. The study aims to determine the addition of calcium carbonate (CaCO3) to the cultivation medium on sand lobster's growth performance and survival. The study was conducted from April to August 2023 at the Vocational School of IPB University and Djuanda University, Bogor. The study used sand lobsters measuring 2.43 ± 0.25 cm in length, weighing 0.22 ± 0.04 g, and with a stocking density of 15 tails/aquarium. During the study, the lobsters were fed shrimp. This study used a completely randomized design (CRD) with three treatments and four replications. The treatments consisted of K (control), AK20 (Dose 20 mg CaCO3/L), and AK40 (Dose 40 mg CaCO3/L). The parameters observed were Specific length growth rate (SLGR), Absolute length growth rate (ALG), Specific weight growth rate (SWGR), Absolute weight growth rate (AWG), and Survival rate (SR). The results showed significantly different results (P<0.05) for SGR and SGR, with the best results being AK20 treatment with an SGR of 1.03±0.32%/day, SGR of 3.46±0.69%/day, SGR of 0.54±0.17 cm, and SGR of 0.23±0.05g. Adding CaCO3 showed no significantly different results (P>0.05) in survival rate with a 73.33-100.00%. The due to internal factors, namely physiological conditions and genetic characteristics.